Enzymatic degradation of cellulose for thermophilic actinomycete: isolation, characterization and cellulolytic activity determination - Ramírez, Pablo (2003)
One hundred and forty five cellulolytic thermophilic actinomycete strains were isolated from 71 compost, soil, hay and dung samples. Streptomyces sp. (50,63%), Thermomonospora curvata (15,82%), T. chromogena (13,92%), and other species were identified. Endoglucanase, exoglucanase and β-glucosidase activities were evaluated from 10 cellulolytic actinomycete strains. Among these the Streptomyces sp. 7CMC10 strain showed the biggest activity levels corresponding to 20,14; 2,61 and 5,40 UI/mg of protein, respectively.